Cloning and Expression of ace Gene of Vibrio cholerae in Escherichia coli - E. V. Monakhova; R. V. Pisanov; L. M. Verkina; A. V. Mironova (Проблемы особо опасных инфекций, 2012)
Accessory cholera enterotoxin (ace) gene of Vibrio cholerae, amplified by PCR, is cloned into the BamHI-HindIII sites using plasmid pQE30. Expression of ace gene is under the control of T5 promotor. The Escherichia coli strain M15[pREP4]pAce90 (KM 194), containing recombinant plasmid, is an active producer of 6His-Ace protein, which possesses biological activity in the models of suckling mice and causes accumulation of fluid in the intestine. The product is contained in inclusion bodies found in the cells of coliform bacterium. The engineered producer strain can be used to obtain Ace preparations with a view to study its significance as pathogenicity factor in cholera vibrio.